Abdominal Obesity and their association with Total Body: Fat Distribution and Composition. Case of Algerian Teenager Male high school students - Mohammed Zerf; Noureddine Atouti; Farouk Abdullah Ben (Physical Education of Students, 2017)
Purpose: Our aim attempted to esteem the impact of abdominal fat on body fat distribution or composition related to total body fat as recommended weight loss among High School Students. Material: For the proposed, 100 male students from the Algerian high school Education Sector's mandate Sidi Bel Abbes, participate in the present study. Their average age 16±1.52 years, distributed into homogeneous groups, according to their body fat percent categories. Examined by saving tests (Body Fat Percentage (BFP) - Abdominal circumference (WC) - Body mass index (BMI)). Results: Based on the test data and the analysis statistics applied, we confirm: a) Abdominal obesity is excess body gain correlate with total fat BMI. It highly affected body composition reported as additional fat for overweight in compare with acceptable according to Ideal BFP categories. b) Abdominal obesity is an amount deep fat correlates to total BFP. It higher influenced the distribution of total body fat reported as additional excess fat among overweight category compared to the acceptable group. c) Waist circumference (WC) is the leading marker of abdominal fat deposits located in the central region of the body. While the combination of body mass index (BMI) and waist circumference (WC), reflects the combined effects of body build (fat or fatness) in individuals at higher risk of excessive body fat. Conclusions: founded on the differences acquired by the research team. We highlight that abdominal obesity is strongly connected to larger WC relate to total body gain located as excess inordinate fatness BMI or fat distribution BFP among our overall sample. Evidence, which guides us to recommend our adolescent students to intensification their hours of sports practice, in order to avoid the consequences of abdominal obesity gain. Announced in the present study as excess abdominal adiposity more metabolically active. Requiring the control of body weight loss (BFP or BMI) strongly correlates to waistline as an ideally accurate measurement of total abdominal fat (visceral & subcutaneous). It's paired with BMI revealed their impact on body build in early adulthood or throughout life.